The Strategic Evaluation of Technology Innovation Opportunities in Waste Strategy Planning - McHenry, Peter P. (Cranfield University, 2004)
Technology innovation is needed to support sustainable waste management systems and innovation should be viewed as a central focus of policy design. The difficulty is that policy is designed at a single point in time where as the environment and the processes of innovation are dynamic. The research investigates the extent to which the design of European Union waste policy and its implementation in the UK stimulates the opportunity for technology innovation. The research investigates how understanding of the relationships between EU waste policy, the process of innovation and technology assessment technique affect the opportunity for technology innovation. The research reviews the development of integrated waste management system models highlighting their limitation in evaluating waste technology options within the wider policy context in an uncertain environment over time. The review identifies their failure to consider the interaction between the financial, environmental, social and operational objectives of new technology. The research describes how failure to simulate system characteristics such as waste process operational demands/constraints, varying spatial resolutions, flexible system boundaries and the uncertain environment over time can affect the opportunity for technology innovation. The research describes the development of a modelling tool addressing these limitations in SIMILE Process Simulation Modelling Software. The model uses the Bedfordshire sub-region of the UK as a case study mapping the flow of waste from generation to disposal. The model calculates a single cost function based on economic, environmental and social costs through, wherever feasible, attributing monetary values to all impacts of any technology. Scenarios are modelled to investigate the extent to which ED waste policy and its implementation affects the opportunity for technology innovation. The model is used to investigate the extent to which relationships between the financial, environmental, social and operational objectives of technology create barriers to new technology. The research identifies how the design, development and application of waste strategy assessment models can influence the opportunity for technology innovation. The research identifies how policy imposes additional cost burdens on the opportunity for technology innovation in the Bedfordshire region. The research concludes by suggesting how policy might be designed to stimulate and support technology innovation.